2017
DOI: 10.1063/1.5010892
|View full text |Cite
|
Sign up to set email alerts
|

Transferrable monolithic III-nitride photonic circuit for multifunctional optoelectronics

Abstract: A monolithic III-nitride photonic circuit with integrated functionalities was implemented by integrating multiple components with different functions into a single chip. In particular, the III-nitride-on-silicon platform is used as it integrates a transmitter, a waveguide, and a receiver into a suspended III-nitride membrane via a wafer-level procedure. Here, a 0.8-mm-diameter suspended device architecture is directly transferred from silicon to a foreign substrate by mechanically breaking the support beams. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Bidirectional optical signal transmission typically requires two sets of optical transmitters and receivers. However, integrating the functionalities of transmitter and receiver into one device, and creating bidirectional optical signal transmission between two identical devices, is important for miniaturized and monolithic optoelectronic systems 1 , 2 . Such dual-functional devices have previously been fabricated with III–V semiconductors 1 , 2 , but their creation using solution-processed semiconductors is of particular interest due to their lightweight, mechanical flexibility, and simple integration with complementary metal–oxide–semiconductor (CMOS) technology 3 7 .…”
mentioning
confidence: 99%
“…Bidirectional optical signal transmission typically requires two sets of optical transmitters and receivers. However, integrating the functionalities of transmitter and receiver into one device, and creating bidirectional optical signal transmission between two identical devices, is important for miniaturized and monolithic optoelectronic systems 1 , 2 . Such dual-functional devices have previously been fabricated with III–V semiconductors 1 , 2 , but their creation using solution-processed semiconductors is of particular interest due to their lightweight, mechanical flexibility, and simple integration with complementary metal–oxide–semiconductor (CMOS) technology 3 7 .…”
mentioning
confidence: 99%
“…Creating bidirectional MIR communication systems using two identical devices facilitates the design of simplified MIR-based optoelectronic systems. Such conceptual advances have been witnessed in visible and near-infrared regions, but not yet in the MIR range 7 , 8 . This is because the majority of traditional MIR detectors and emitters, e.g., narrow-band gap semiconductors 9 , 10 , are predominantly designed to be either emitters or detectors, and, therefore, are not compatible for dual-functionality with satisfactory performance.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported the monolithic integration of photodiodes, LEDs, and waveguides for applications in visible light communication [30,31]. Wang et al conducted in-plane data transmission among a transmitter (LED), waveguide, and receiver (photodiode) [32,33]. Liu et al reported the monolithic integration of high electron mobility transistors, LEDs, and two types of photodiodes by selective-area epitaxy [34].…”
Section: Introductionmentioning
confidence: 99%